Faktor-faktor yang mempengaruhi produksi budidaya tambak udang vaname (litopenaeusvannamei) di Kecamatan Wundulako Kabupaten Kolaka - Pisi, Diana; Budiyanto; Riani, Irdam (Jurnal Sosial Ekonomi Perikanan, 2021)
This research was conducted in July 2019 in Wundulako District, Kolaka Regency and aims to determine the factors that affect the production of vaname shrimp culture and how the influence of production factors on the production of vaname shrimp. The research location was done by purposive. The population in this study were all farmers of vaname shrimp cultivation in Wundulako District, amount17 people. Determination of the sample was carried out by census so that the number of samples was 17 cultivators. Data were collected through direct interviews using questionnaire prepared, the observed data included: respondent identity, age, education, business experience, and production inputs used in the vannamei shrimp cultivation (land area, number of shrimp fry, amount of feed, amount of fertilizer, labor and production quantities). Data were analyzed using multiple non-linear regression with the SPSS 16.0 program. The results of the studywas concluded that the factors had a significant and positive effect on vaname shrimp production were the number of shrimp fry, the amount of feed and the amount of fertilizer. Meanwhile, the unsignificant factor and negative are the land area ​​ and labor.